2020
DOI: 10.1515/tjb-2019-0184
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary case-based small group discussions to integrate basic medical sciences with clinical situations

Abstract: ObjectivesIntegration of the basic medical sciences with clinical medicine motivates medical students by showing how the fundamental concepts they have learned will come into their future practice. In this context, we created clinical integration sessions (CIS) in our first-year medical curriculum.MethodsThe instructors of different disciplines wrote the clinical scenarios together. The scenarios were discussed in five sessions with 39 first-year students. The first session’s scenario consisted of four brief “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Students also have positive perceptions toward small-group effectiveness, particularly in learning experience and teamwork (Sahu et al, 2018). They learn how to apply the principles of basic medical sciences to clinical medicine, which motivates them for further learning (Hadimani, 2014;Naveed et al, 2017;Semin, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Students also have positive perceptions toward small-group effectiveness, particularly in learning experience and teamwork (Sahu et al, 2018). They learn how to apply the principles of basic medical sciences to clinical medicine, which motivates them for further learning (Hadimani, 2014;Naveed et al, 2017;Semin, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Semin et al (2018) implemented multidisciplinary case-based small group discussions to integrate basic medical sciences with clinical situations for 39 students in 5 body systems and found that 62% of students find the integrated cases useful for their learning. 12 They carried out discussions on 3 hours sessions and without enough prior knowledge for students and set the outcomes for each case. Our study was carried out on a larger number of participants (694), and students were the main drivers of their learning process, and they had previous knowledge from all disciplines and we derived the outcomes from the curriculum that is required to be evaluated and improved to report the deficiencies present and avoid confusing students with them.…”
Section: Discussionmentioning
confidence: 99%